Co-designing with engineers for community engagement in rural Uganda. (4th May 2023) - White, P. J.; Okello, Dorothy; Casey, Brian P.; Najjuuko, Claire; Lukanga, Ronald
Abstract: Co-design is seen as crucial for designing solutions for resource-constrained people living in developing countries. To best understand their needs, user engagement and co-design strategies need to first be developed. In this Design Practice Brief, a process of co-design was created and used to understand ways telecommunication engineers could engage with rural communities in Uganda. It reports and reflects on (i) the experience of co-designing with nondesigners and (ii) creating a co-design structure and developing co-design methods of engaging with community members living in developing countries. In doing so, it offers a format and case study for future practitioners facilitating and conducting co-design with nondesigners and contributes to a knowledge gap in the reporting and reflection of co-design practice. This case study is unique as the co-design practice was achieved remotely (online), crossed disciplines (designers and telecommunication engineers) and cultural boundaries (European and African). It finds that in co-designing with nondesigners, preparation and structure are key, with acknowledgement and management of cultural and discipline differences.